Comparative anatomy of the gill skeleton of fossil Aulopiformes (Teleostei: Eurypterygii). (14th November 2018) - Beckett, Hermione; Giles, Sam; Friedman, Matt
Abstract : Gill skeletons provide a rich source of character information for inferring the relationships among extant fishes. However, the difficulties in accessing branchial structures in fossils have limited the use of gill-arch anatomy in phylogenetic studies of extinct fishes. Here we apply micro-computed tomography (µCT) to visualize and describe gill-arch anatomy in three-dimensionally preserved Late Cretaceous–early Palaeogene remains of seven genera attributed to the eurypterygian clade Aulopiformes (lizardfishes), a group for which detailed cladistic character sets describing patterns of variation in the branchial skeleton are available. We evaluate the placement of these fossil taxa based on characters of the gill skeleton in isolation. Our results support an alepisauroid placement for † Apateodus corneti, † Cimolichthys lewesiensis and † Halec eupterygius, and a stem synodontid affinity for † Argillichthys toombsi and † Labrophagus esocinus . These placements are broadly consistent with past hypotheses based either on formal cladistic argumentation or qualitative morphological comparison drawing on other skeletal systems. We find insufficient evidence in the branchial skeleton to place † Aulopopsis depressifrons more specifically than Aulopiformes incertae sedis . Gill-arch anatomy substantially revises past interpretations of † Sardinioides illustrans by providing clear evidence for placement within Aulopiformes generally, and as either a stem aulopid or stem paralopid more specifically. This species must therefore be removed from † Sardinioides, the type of which is a myctophiform and shows conspicuous anatomical differences from †' S .' illustrans . Our work provides proof-of-concept for the recovery of detailed information on gill skeleton anatomy in fossils, indicating the potential for the extraction of considerable new morphological data – and phylogenetic information – from suitably preserved fossil specimens.